2018
DOI: 10.1063/1.5024321
|View full text |Cite
|
Sign up to set email alerts
|

Proof of concept for an optogalvanic gas sensor for NO based on Rydberg excitations

Abstract: We demonstrate the applicability of 2-photon Rydberg excitations of nitric oxide (NO) at room temperature in a gas mixture with helium (He) as an optogalvanic gas sensor. The charges created initially from succeeding collisions of excited NO Rydberg molecules with free electrons are measured as a current on metallic electrodes inside a glass cell and amplified using a custom-designed highbandwidth transimpedance amplifier attached to the cell. We find that this gas sensing method is capable of detecting NO con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…For example, atom-based sensors have been used for precise measurements of magnetic fields [21,22] and gravity [23,24] and are beginning to be marketed and used in fields as diverse as biomedical sensing [25], geomagnetic [26], and defense applications [27]. A subclass of atom-based sensors includes those based upon Rydberg atoms, atoms that have been excited to a high principal quantum number n. It has been shown that Rydberg atoms are excellent sensors for weak electromagnetic fields in the radio-frequency, microwave, and THz ranges [28][29][30][31], as well as for trace gas detection [32]. Recently, the ability of Rydberg atoms to provide IRto-optical conversion has been exploited [33][34][35], and imaging of high-power pulsed IR [36] and THz [37] fields has been demonstrated using a Rydberg atom photocathode.…”
Section: Introductionmentioning
confidence: 99%
“…For example, atom-based sensors have been used for precise measurements of magnetic fields [21,22] and gravity [23,24] and are beginning to be marketed and used in fields as diverse as biomedical sensing [25], geomagnetic [26], and defense applications [27]. A subclass of atom-based sensors includes those based upon Rydberg atoms, atoms that have been excited to a high principal quantum number n. It has been shown that Rydberg atoms are excellent sensors for weak electromagnetic fields in the radio-frequency, microwave, and THz ranges [28][29][30][31], as well as for trace gas detection [32]. Recently, the ability of Rydberg atoms to provide IRto-optical conversion has been exploited [33][34][35], and imaging of high-power pulsed IR [36] and THz [37] fields has been demonstrated using a Rydberg atom photocathode.…”
Section: Introductionmentioning
confidence: 99%
“…Here, by preparing long-lived hydrogenic Rydberg states, for which predissociation is not the dominant decay mechanism, by two-color two-photon excitation from the X 2 Π 1=2 ground state [53][54][55][56], we report Rydberg-Stark deceleration and electrostatic trapping of NO. NO is a chemically important radical that plays a role in atmospheric physics, combustion, and trace gas detection [57]. Measurements of the decay of the trapped molecules in environments maintained at T env ¼ 295 and 30 K, and after initial excitation to states with principal quantum numbers ranging from n ¼ 38 to 44, provide new insights into the lifetimes and slow decay processes of Rydberg states of NO.…”
mentioning
confidence: 99%
“…Here, by preparing long-lived hydrogenic Rydberg states, for which predissociation is not the dominant decay mechanism, by two-color two-photon excitation from the X 2 Π 1/2 ground state [53][54][55][56], we report Rydberg-Stark deceleration and electrostatic trapping of NO. NO is a chemically important radical that plays a role in atmospheric physics, combustion and trace gas detection [57]. Measurements of the decay of the trapped molecules in environments maintained at T env = 295 and 30 K, and after initial excitation to states with principal quantum numbers ranging from n = 38 to 44, provide new insights into the lifetimes and slow decay processes of Rydberg states of NO.…”
mentioning
confidence: 99%